Zika and cases of microcephaly in the state of Zulia: clinical and epidemiological aspects of the sprout, year 2016 - María Gómez; Ayarí Avila; Elina Castillo; Angelina Marquez; Nelys Barboza; Belen Rodríguez; Luisa Marquez; Gisbel Ferrer; Manuel Gómez (Kasmera, 2018)
Zika is an emerging disease in Venezuela and in the state of Zulia, it generally evolves in a benign manner and can produce complications such as Guillain-Barré syndrome and microcephaly in newborns. Itis proposed to describe the clinical and epidemiological aspects of the Zika outbreak and the cases of microcephaly. The research is descriptive, cross-sectional, conducted from May 2016 to March 2017. The population consisted of 1,155 suspected cases, with a sample of 228 patients, resulting in 108 positive PCR in real time. The largest number of cases occurred at the age of 17 to 33 years (59.3%), with a predominance of females (81.5%), in the municipalities of Maracaibo and San Francisco (75%). In relation to the symptomatology, the frequent are rash (84.3%), headache and fever (76.9%), while arthralgia (65.7%) and myalgia (47.2%) are less common. During the outbreak, there were two deaths of the male sex, representing 1.9%; 146 cases with Guillain-Barré syndrome and 7 cases with microcephaly, corresponding to the male sex (85%), with a newborn gestational age of 37.4 weeks and 85% survival. The main recommendation should be directed to the control of the transmitting vector of the disease and to make the diagnosis of the suspicious cases for their confirmation.